Improving COVID-19 vaccination centre operation through computer modelling and simulation - Wood, Richard M.; Moss, Simon J.; Murch, Ben J.; Davies, Chris; Vasilakis, Christos (Health systems, 2025)
Mass vaccination has provided a route out of the COVID-19 pandemic in a way that social restrictions can be safely eased. For many countries, dedicated vaccination centres have been key to that effort. However, with no directly comparable historical experience there has been little information to guide the operational management and initial configuration of these sites. This paper provides an account of how, early in the mass vaccination effort, Operational Research has been a valuable asset in supporting management decisions at two major vaccination centres in the UK. We first describe a conceptual pathway model representing the key stages of the vaccination process, from registration to clinical assessment, vaccination, and observation. An approximation using discrete event simulation is then presented. On application, we report on its use in influencing the initial setup of one site, with model outputs directly setting the daily number of patient bookings. For the same site, we reveal how analysis has informed a significant operational shift in combining two key activities on the vaccination pathway (clinical assessment and vaccination). Finally, we describe how, at a second site, modelling has examined pathway stability, in terms of resilience to unforeseen "shocks" such as delayed arrivals and staff unavailability.